Efek Akuntabilitas Dalam Memediasi Kualitas Pelaporan Keuangan Dan Kinerja Desa Di Madura - Hanif Yusuf Seputro; Erfan Muhammad (Jurnal Penelitian Teori dan Terapan Akuntansi (PETA), 2022)
Observing the New Public Management (NPM) theory and agency theory, this study examines the mediating role of accountability in the relationship between financial reporting quality and the performance of public organizations in this case are villages in Madura. The research model and hypotheses were tested by surveys and responses obtained from financial managers and village leaders, in this case the village heads in villages throughout Madura. The results of the study directly that the quality of financial reporting and accountability have a significant effect on village performance. The analysis indirectly results in accountability being able to mediate the quality of financial reporting on village performance in Madura. Suggestions in this study are: 1) Villages maximize village programs according to village goals; 2) Villages must be able to make quality financial reports in order to improve village performance for the better; 3) When financial reports are implemented with a higher quality through optimizing accountability, village performance can be further improved for the better.